Frequency and Predictors of Pneumonia After Isolated Coronary Artery Bypass Grafting (CABG): A Single-Center Study - Ozgur Baris; Tugba Asli Onyilmaz; Huseyin Kaya (Diagnostics)
Background: CABG is a commonly performed procedure to improve survival and quality of life in patients with coronary artery disease. Despite advances in surgical techniques and perioperative care, postoperative pneumonia remains a serious complication contributing to increased morbidity, mortality and healthcare costs. This study aims to evaluate the incidence of postoperative pneumonia (POP) and identify its risk factors in patients undergoing isolated CABG. Methods: This retrospective study analyzed 430 patients who underwent CABG between 2019 and 2024. Patient demographics, clinical characteristics, surgical details and laboratory data were collected. Statistical analysis included univariate and multivariate logistic regression to identify significant predictors of pneumonia. Results: The incidence of POP after CABG was 10% (43/430). In patients with POP, diabetes mellitus (p = 0.03) and chronic kidney disease (p = 0.048) prevalence was higher, cardiopulmonary bypass (CPB) (p = 0.01) and cross-clamp time (p = 0.003) was longer, LDH levels (p = 0.017) were higher, hemoglobin (p = 0.012) and albumin (p = 0.015) levels were lower, and lymphocyte % (p = 0.04) was lower; prevalence of COPD and length of stay (LOS) in hospital tended to be higher (both p < 0.06). Multivariate binary logistic regression identified COPD (OR 4.383, 95% CI: 1.106–17.363, p = 0.035), CPB time (OR 1.013, 95% CI: 1.001–1.025, p = 0.030) and LOS (OR 1.052, 95% CI: 1.004–1.103, p = 0.035) as independent predictors of POP. Conclusions: Postoperative pneumonia is a common complication after CABG and is strongly associated with preoperative COPD, CPB time and length of stay in hospital. These findings underline the importance of preoperative risk assessment and optimization. Early identification of high-risk patients may allow targeted strategies such as enhanced respiratory support and prophylactic antibiotics to reduce the incidence of pneumonia and improve clinical outcomes.